'Ijtihad' and 'Relevance of Sharia' to Contextualize Universal Human Rights Discourse. Issue 4 (November 2013) - Corrao, Francesca M.
Abstract : In spite of this promising theoretical background, the acceptance and implementation of the human rights regime in Islamic societies is still controversial. One major issue in the conceptualization as well as in the practice of human rights in Islamic countries is surely related to the tension between the alleged universal validity of these standards and the limits of internal state sovereignty.